2013
DOI: 10.1002/jib.85
|View full text |Cite
|
Sign up to set email alerts
|

Storage stability of pasteurized non-filtered beer

Abstract: The influence of pasteurization on non-filtered beers was investigated during accelerated storage (40°C, 41 days). Two beers were produced from the same hopped wort, which was fermented with two different yeast strains. Half of the bottled beers were tunnel pasteurized resulting in four different beer samples. The pasteurization influenced the volatile profile of both fresh beers, but during storage the differences between the volatile profiles of pasteurized and non-pasteurized beers disappeared. During the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Similarly, He et al (2012) observed around 10% lower antioxidant activity in fresh cloudy wheat beer over the first 18 days of storage at 20°C. Lund et al (2012) and Hoff et al (2013) showed that the radical formation during storage occurs faster in unpasteurised than in pasteurised beer, and that beer pasteurisation greatly improves oxidative stability. However, Cao et al (2011) observed that if pasteurization intensity is too severe, this may result in lower polyphenol content and reduced oxidative stability.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, He et al (2012) observed around 10% lower antioxidant activity in fresh cloudy wheat beer over the first 18 days of storage at 20°C. Lund et al (2012) and Hoff et al (2013) showed that the radical formation during storage occurs faster in unpasteurised than in pasteurised beer, and that beer pasteurisation greatly improves oxidative stability. However, Cao et al (2011) observed that if pasteurization intensity is too severe, this may result in lower polyphenol content and reduced oxidative stability.…”
Section: Resultsmentioning
confidence: 99%
“…Decreased TA might be explained by the precipitation of organic acids (and salts thereof) during freezing, but the increased TA observed for beer A and cider A could not be explained. The phenolic composition of sparkling wine was not affected by refrigeration or freezing, but decreases of up to 10% Beverages 2016, 2, 26 5 of 11 were observed for beer and cider samples following long-term freezing, and by approximately 40% in the case of beer D. Refrigeration and freezing were not expected to influence alcohol or sugar content, nor color, given that previous research has demonstrated the color stability of juice samples during storage [25].…”
Section: Resultsmentioning
confidence: 78%
“…Degassed beer containing N ‐tert‐butyl‐ α ‐nitrone (30 m m ) was heated at 60°C in closed Blue Cap bottles with headspace of atmospheric air. Subsequently the samples were analysed with the same settings as previously described at given time intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Electron spin resonance (ESR) measurement techniques were employed to monitor changes in the generation of free radicals with regard to various levels of pasteurization. The measurements were performed according to Hoff et al with an EMX‐8/2.7 ESR spectrometer (Bruker, German). Wheat beer samples were degassed by stirring with 1‐octanol (0.01%) on a magnetic stirrer for 5 min and filtered through a funnel filter.…”
Section: Methodsmentioning
confidence: 99%